KARAKTERISTIK KIMIA TANAH GAMBUT YANG DIAMELIORASI DENGAN BIOCHAR TONGKOL JAGUNG SEBAGAI MEDIA TUMBUH BAWANG PUTIH - Susana, Rini; Anggorowati, Dini; Zulfita, Dwi; Warganda, Warganda; Nurjani, Nurjani (Fakultas Pertanian, Universitas Janabadra, 2023)
Biochar added to peat media will affect changes in soil chemical properties such as an increase in pH, organic C, total N, total P, total K, basic cations such as Ca, Mg, Na, CEC and base saturation. These changes will affect nutrient uptake, growth and yield of garlic. Biochar application with the right dose needs to be known so that it would be efficient and economical in biochar utilization. The aim of the study was to know the chemical characteristics of peat soil ameliorated with corn cob biochar and to find the effective dose of biochar for growth and yield of garlic.This research was conducted at the experimental field of the Faculty of Agriculture, Tanjungpura University, Pontianak. The experiment used a completely randomized design, consisting of 5 treatments, each treatment consisting of 4 replications. The treatments were: b1 = without biochar; b1 = 50 g/polybag; b2=100g/poly bag; b3= 150 g/polybag and b4= 200 g/polybag. The observed variables ware chemical characteristics of the peat media including pH, organic C, total N, C/N, available P, Base saturation, CEC, Ca, Mg, K, Na, Pb, Cd. Other observations were plant dry weight, tuber dry weight, N, P, K, Pb and Cd content in garlic plant tissue. The results showed that the application of biochar did not cause significant changes in pH, C-Organic and Total N, but the addition of biochar doses tended to further increase the levels of P in the soil. The application of biochar increased the available K and Na levels and soil base saturation, but the Ca and Mg levels, available Ca and Mg levels tended to decrease with increasing doses of biochar. The dry weight of garlic plants increased with increasing doses of biochar. The dose of 200 g of biochar was the most effective for the growth and yield of garlic bulbs on peat soil. Keywords: Garlic, Corncob Biochar, Peat INTISARI Biochar yang ditambahkan pada media gambut akan mempengaruhi perubahan sifat kimia tanah seperti peningkatan pH, C organik, N total, P total, K total, kation-kation basa seperti Ca, Mg, Na, KTK dan Kejenuhan Basa. Perubahan-perubahan ini akan mempengaruhi serapan hara dan pertumbuhan serta hasil bawang putih. Pemberian dengan dosis yang tepat perlu diketahui agar effisien dan ekonomis dalam pemanfaatan biochar. Tujuan penelitian mengkaji karakteristik kimia tanah gambut yang diameliorasi dengan biochar tongkol jagung dan mencari dosis biochar yang effektif untuk pertumbuhan dan hasil bawang putih. Penelitian ini dilaksanakan di Kebun Percobaan Fakultas Pertanian Universitas Tanjungpura Pontianak. Percobaab menggunakan Rancangan Acak Lengkap, terdiri dari 5 perlakuan, setiap perlakuan terdiri dari 4 ulangan.Perlakuan tersebut: b1= tanpa biochar; b1 = 50 g/polibag; b2=100 g/polibag; b3= 150 g/polibag dan b4= 200 g/polibag. Variabel pengamatan meliputi perubahan karakteristik kimia media gambut meliputi pH, C organik, N total, C/N, P tersedia, KB, KTK, Ca-tersedia, Mg-tersedia, K tersedia, Na-tersedia, Pb total, Cd total. Pengamatan lainnya adalah berat kering tanaman, berat kering umbi, kandungan N, P, K, Pb dan Cd pada jaringan tanaman bawang putih. Hasil penelitian menunjukkan pemberian biochar tidak menyebabkan perubahan yang signifikan pada pH, C-Organik dan N Total, namun penambahan dosis biochar cenderung semakin meningkatkan kadar P2O5 pada tanah. Pemberian biochar meningkatkan kadar K dan Na tersedia serta Kejenuhan Basa tanah, namun kadar Ca dan Mg, kadar Ca dan Mg tersedia cenderung menurun dengan meningkatnya dosis biochar. Berat berat kering tanaman bawang putih meningkat dengan meningkatnya dosis biochar. Dosis 200 g biochar adalah yang paling effektif untuk pertumbuhan dan hasil umbi bawang putih di tanah gambut. Kata Kunci: Bawang Putih,Biochar Tongkol jagung, Gambut